The multifaceted anti-atherosclerotic properties of herbal flavonoids: A comprehensive review - Meiwen Huang; Xuena Xie; Rong Yuan; Qiqi Xin; Shudong Ma; Hongai Guo; Yu Miao; Chunyu Hu; Yizhun Zhu; Weihong Cong (Pharmacological Research)
Atherosclerosis (AS) is a major etiological factor underpinning a spectrum of cardiovascular diseases, leading to cerebral infarction, coronary artery disease, and peripheral vascular disease. The chronic progression of AS, spanning from initial plaque formation to the occurrence of acute cardiovascular events, underscores the complexity of AS and the challenges it presents in terms of treatment. Currently, the clinical management of AS relies predominantly on statins and proprotein convertase subtilisin/kexin type 9 inhibitors, which primarily aim to reduce low-density lipoprotein levels and have demonstrated some therapeutic efficacy. Nevertheless, due to their potential side effects, there is a pressing need to actively investigate alternative treatment approaches. Researches on natural compounds derived from herbal medicines, such as flavonoids, hold significant promise in combating AS by regulating lipid metabolism, reducing oxidative stress and inflammation, inhibiting the proliferation of vascular smooth muscle cells, modulating autophagy and additional pathways. Various targets participate in these physiological processes, encompassing acyl-CoA: cholesterol acyltransferase (ACAT), ATP citrate lyase (ACLY), nuclear factor erythroid 2-related factor 2 (Nrf2), krüppel-like factor 2 (KLF2), NOD-like receptor protein 3 (NLRP3), transcription factor EB (TFEB) and so on. This comprehensive review endeavors to synthesize and analyse the most recent findings on herbal flavonoids, shedding light on their anti-atherosclerotic potential and the underlying protective mechanisms and related-targets, which might pave the way for the development of novel drug candidates or the optimization of flavonoid-based therapies.